2004
DOI: 10.1002/jat.992
|View full text |Cite
|
Sign up to set email alerts
|

Sidestream tobacco smoke as the main predictor of exposure to polycyclic aromatic hydrocarbons

Abstract: Polycyclic aromatic hydrocarbons (PAHs) were measured in mainstream and sidestream tobacco smoke from 14 commercial brands of cigarettes purchased in Italy during 2001-2002. The PAHs detected in smoke and analysed with HPLC and a fluorimetric detector were: fluoranthene, pyrene, benzo[a]anthracene, chrysene, benzo[a]pyrene, benzo[b] fluoranthene, benzo[k] fluoranthene, benzo[g,h,i]perylene and dibenzo[a,h]anthracene. The PAH levels in mainstream smoke from different cigarette brands obtained using an official … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 20 publications
3
67
3
1
Order By: Relevance
“…Estimates of daily intake of both BaP (0?19 mg/d) and total PAH (9?28 mg/d) in this population of pregnant women were in a range comparable to levels previously reported in Spain (13,14,17) and other European countries (3,(24)(25)(26) . For example, our estimates of dietary BaP (3,13,14,17,(24)(25)(26)(27) .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Estimates of daily intake of both BaP (0?19 mg/d) and total PAH (9?28 mg/d) in this population of pregnant women were in a range comparable to levels previously reported in Spain (13,14,17) and other European countries (3,(24)(25)(26) . For example, our estimates of dietary BaP (3,13,14,17,(24)(25)(26)(27) .…”
Section: Discussionsupporting
confidence: 86%
“…For example, our estimates of dietary BaP (3,13,14,17,(24)(25)(26)(27) . Such differences could be explained by disparities in dietary habits or the populations studied (all adults, adult women v. pregnant women), but may also be due to differences in the methods used to assess dietary intake or estimates of PAH concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, consistent with our findings in children, Tsai et al (53) reported an average 9.6% increase in urinary 1-OHPyr in preschool children per one cigarette smoked by the child's father. The higher concentrations of urinary PAH metabolites in nonsmokers who are involuntary exposed to tobacco smoke compared with unexposed can be related to high PAH levels in the sidestream fraction of tobacco smoke, the main fraction to which nonsmokers are exposed (54)(55)(56).…”
Section: Pah Exposure-comparison With Other Countriesmentioning
confidence: 99%
“…For examples, the growth of rat follicles cultured in vitro was impeded by the presence of B[a]P (Lodovici et al, 2004;Neal et al, 2007). Moreover, administration of this toxicant signifi cantly reduced follicle diameter and attenuated FSH stimulated growth in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%